A heuristic solution to the optimisation of flutter control in compression systems (and to some more binary quadratic programming problems) via ΔΣ modulation circuits - Callegari, S; Bizzarri, F (2010 IEEE International Symposium on Circuits and Systems (ISCAS), 2010)
An example of how circuit related techniques can help solving optimisatin problems originating from completely different domains is provided. It is shown that a specific class of Unconstrained Binary Quadratic Programming (UBQP) problems, including those arising in the optimisation of flutter control via blade mistiming, can be solved by means of ΔΣ modulators. This is done in steps, first restating the UBQP problem as a specific signal processing problem, and then attacking the latter via the design of a ΔΣ modulator with a suitably derived Noise Transfer Function. A (heuristically) optimal solution for the original problem is finally obtained from the modulator output stream. The method is validated by two numerical examples arising in the design of turbo-machines.